A remark on stationary fuzzy metric spaces - Savchenko, A. (Carpathian Mathematical Publications, 2011)
The main result states that the category of stationary fuzzy metric spaces (with respect to an archimedean t-norm) and nonexpanding maps is isomorphic to a full subcategory of the category of metric spaces and nonexpanding maps. The case of non-archimedean t-norms is also discussed.